Performance Management Practices: A Decisive Approach to Improve Employee Productivity - et.al, Shalini Dixit (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Performance management practices include various approaches to significantly assess the organizational performance and productivity. It includes critical analysis and evaluation of employees skills and knowledge to increase output at workplace which establishes culture of proper evaluation of individual performance i.e. directly linked with attainment of individual as well as organizational goal. With the changing dimensions of business operations performance of employees is ensured through involvement of strategic approaches which enables them to understand the required standards of performance and evaluation criteria to assess productivity with merits and demerits of learning and improving better alternatives which ultimately enhances the overall performance of organization. This study helps in critical assessment of various performance management practices and its effect on employee productivity in textile firms of Bhilwara city. The performance management practices comprised of employee appraisal system, training and development, reward system and feedback which all are considered as independent variables and dependent variable is defined as employee productivity. The research paper incorporates primary data collected through a structured questionnaire from a sample size of 100 respondents who worked at various managerial levels in textile firms. A descriptive research design is used for the analysis of data with the help of mean, standard deviation and regression analysis to accomplish the research objective of assessing the effect of independent variables performance appraisal, training & development, reward system and feedback on employee productivity. Various hypothesis are framed to test the results and draw inferences for the population. The study focuses on implementation of various approaches that can enhance employee productivity and develop a workforce through proper training and evaluation with the help of review and feedback mechanism and ensure growth of individuals as well as organization and fulfilment of organizational goals. The result is analysed through regression which helps in adoption of sustainable HR practices forced to rethink on decisions pertaining to employee productivity